2011
DOI: 10.1590/s0101-31222011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Época de colheita e secagem na qualidade de sementes de pimenta Habanero Yellow

Abstract: As pimentas constituem um dos principais produtos da olericultura brasileira. O interesse das indústrias por espécies picantes, como a pimenta Habanero, tem crescido a cada ano, sobretudo para a produção de molhos e preparados desidratados, o que aumentou a demanda no mercado por sementes de qualidade. O autor teve, através desta pesquisa, por objetivo avaliar os efeitos das épocas de colheita das sementes e da secagem na qualidade das sementes de pimenta Habanero Yellow. Foram utilizadas sementes extraídas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 22 publications
2
22
0
12
Order By: Relevance
“…Vidigal et al (2011) also found that no seed germination of hot peppers of the Amarela Comprida variety occurred before 40 DAA. These results corroborated the findings of Queiroz et al (2011), who stated that the seeds removed from immature hot peppers showed low or no germination. At 55 DAA (yellowish green peppers), the hot pepper seeds started germinating, with 40% normal seedlings obtained ( Figure 3a); at 70 DAA (red peppers), the germination increased, averaging 87%, which was sustained until 100 DAA (intense red peppers; Figure 3a).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Vidigal et al (2011) also found that no seed germination of hot peppers of the Amarela Comprida variety occurred before 40 DAA. These results corroborated the findings of Queiroz et al (2011), who stated that the seeds removed from immature hot peppers showed low or no germination. At 55 DAA (yellowish green peppers), the hot pepper seeds started germinating, with 40% normal seedlings obtained ( Figure 3a); at 70 DAA (red peppers), the germination increased, averaging 87%, which was sustained until 100 DAA (intense red peppers; Figure 3a).…”
supporting
confidence: 90%
“…Several research studies have reported the harvest season effects on species of the Solanaceae family, including tomato VIDIGAL et al, 2006), hot peppers (VIDIGAL et al, 2009a;QUEIROZ et al, 2011;VIDIGAL et al, 2011;ABUD et al, 2013;RICCI et al, 2013;PEREIRA et al, 2014), and eggplant (MARTINS et al, 2012). Vidigal et al (2009a) assessed peppers of the Amarela Comprida (C. annuum L.) variety harvested on 40, 50, 60, and 70 days after anthesis (DAA) and stored for 3, 6, 9, 12, and 15 days and found the best germination and vigor resulted in seeds from peppers harvested on 60 DAA that were not subjected to postharvest storage.…”
mentioning
confidence: 99%
“…Foram utilizadas quatro subamostras de 50 sementes de cada cultivar. Foram realizadas avaliações diárias a partir do início da emergência, tendo-se computado o número de plântulas emergidas até a estabilização do estande (Queiroz et al, 2011).…”
Section: Methodsunclassified
“…Entre essas se destacam as de Sanchez et al (1993), com pimentão; Martins et al (2006), com mamão; Vidigal et al (2006), com tomate; Castro, Godoy e Cardoso (2008), com quiabo; Vidigal et al (2009), com pimenta, cv. Amarela Comprida;Queiroz et al (2011), com pimenta Habanero.…”
Section: Introductionunclassified